How agglomeration in the financial services industry influences economic growth: Evidence from Chinese cities - Lin Liang; Shanglang Lin; Yong Li (Kiel Institute for the World Economy (IfW), 2014)
This paper empirically tests the effect of financial knowledge spillovers on agglomeration in China's financial services industry and examines the external effects on cities' economies. The authors apply hierarchical linear modeling to examine a data set that comprises 276 Chinese cities and draw the following conclusions. Firstly, they find that agglomeration in the financial services industry and the Jacobs spillovers of industry diversification both promote financial knowledge spillovers in terms of industry specialization. Secondly, agglomeration in this studied industry has a significant positive influence on a city's economic growth, while financial knowledge spillovers have a significant but negative effect on a city's economic growth. Thirdly, the tendency towards agglomeration in the financial services industry in a few major cities is clear and the clustering significantly influences cities' boundaries. Finally, China's financial services industry is limited by a serious degree of regulation and is dominated by the main banking institutions.
Keywords: G20; O4; 330; financial services industry agglomeration; industry specialization; knowledge spillovers; city economies; hierarchical linear modeling